EFEK IMUNOMODULATOR EKSTRAK ETANOL KULIT BUAH NANAS (Ananas comosus L.Merr) TERHADAP MENCIT PUTIH JANTAN DENGAN METODE BERSIHAN KARBON (Carbon Clearance) - Masayu Azizah; Wiwik Wiraningsih; Ema Ratna Sari (Universitas Padjadjaran, 2017)
AbstractThis research was aimed to study the immunomodulatory effect of ethanol extract of pineapple (Ananas comosus L. Merr) peel on white male mice with carbon clearance method. Animals were divided into 5 groups: Group 1 was given tween 80 1 % v/v;Ggroup 2 was given meniran extracts; Group 3, 4 and 5 were given ethanol extracts of pineapple peel with a dose of 125 mg/kg BW, 250 mg/kg BW, and 500 mg/kg BW,respectively, for 6 days orally. On the 7th day the animals were injected with carbon suspension 0.2 ml/20g BW at the tail vein. Blood was taken at 5th and 15th minutes using capillary pipe from the animal’s orbital retro vein, then it was diluted with 4 ml of 0.1% b/v sodium carbonate and measured its absorbance at 675 nm using visible spectrophotometer. The ethanol extract of pineapple peel showed immunomodulatory effect where the best dose was 250 mg/kg BW. Keywords : biological response modifiers, immunomodulatory, pineapple peel